1993
DOI: 10.1038/ki.1993.102
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of interleukin-1β during hemodialysis

Abstract: It is still controversial whether the hemodialysis (HD) procedure is an inflammatory process in vivo. Therefore, we studied the gene expression of interleukin-1 beta (IL-1 beta) as a marker of inflammation in peripheral blood mononuclear cells (PBMC) of patients during HD by Northern blotting and polymerase chain reaction. Compared to PBMC separated pre-HD (1.0 densitometric units), the amount of IL-1 beta mRNA was increased in PBMC leaving the dialyzer (12.2 +/- 2 densitometric units, P < 0.01), but was not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 32 publications
8
65
0
1
Order By: Relevance
“…However, the invivo observations are more difficult to reconcile with that hypothesis, since only some [38][39][40] but not all [41][42][43] studies reveal increased concentrations of IL-1 P in blood. In line with our observation of a more pronounced PLA 2 activation possibly mediated through IL-1 release with a more complementactivating membrane is the recent report from Schindler et ah [14] demonstrating an increased gene expression of IL-1 (3 in peripheral blood mononuclear cells leaving the dialyser 5 min after start of haemodialysis. These authors found a significant correlation between the increase in IL-ip mRNA and increase in activated complement C5a.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, the invivo observations are more difficult to reconcile with that hypothesis, since only some [38][39][40] but not all [41][42][43] studies reveal increased concentrations of IL-1 P in blood. In line with our observation of a more pronounced PLA 2 activation possibly mediated through IL-1 release with a more complementactivating membrane is the recent report from Schindler et ah [14] demonstrating an increased gene expression of IL-1 (3 in peripheral blood mononuclear cells leaving the dialyser 5 min after start of haemodialysis. These authors found a significant correlation between the increase in IL-ip mRNA and increase in activated complement C5a.…”
Section: Discussionsupporting
confidence: 79%
“…Previous investigations revealed similar peaks of biological events during the initial 15 min on dialysis. These changes comprise among others, a decline in the leuko-ĉ yte count in peripheral blood, evidence for activation of the complement system, release of TNF and interleukins, including IL-ip and arachidonic acid metabolites, such as PGE 2 , TXB 2 , PAF and HETS [2,[8][9][10][11][12][13][14][15][16][17]. The release of many arachidonic acid derivatives suggests activation of PLA 2 , as shown by the present investigations.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, the patients with normal liver enzyme levels during HDcan still develop progressive liver disease after renal transplantation (5,15). Expression of interleukin-1 (3 and tumor necrosis factor-oc (TNF-a) as well as expression of their inhibitors such as interleukin-1 0 and soluble receptors of TNF-a have been shown to be elevated in HDpatients (16,17). Such an imbalance between cytokines and their inhibitors mayplay a pivotal role in the multifaceted process of immune dysfunction in HDpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Since the HCV core region has several epitopes which play a crucial role in the immuneresponse to HCV (25,26), alterations or a deletion in this region in HDpatients can operate on escape from immunepressure, leading to persistence of viral infection. Furthermore, the reduced immunedefense resulting from an imbalance between cytokines and their inhibitors (16,17) might also be involved in viral persistence in HDpatients.…”
Section: Discussionmentioning
confidence: 99%